2013
DOI: 10.1128/iai.00032-13
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ficolin-A and Lectin Complement Pathway in the Innate Defense against Pathogenic Aspergillus Species

Abstract: Aspergillus species are saprophytic molds causing life-threatening invasive fungal infections in the immunocompromised host. Innate immune recognition, in particular, the mechanisms of opsonization and complement activation, has been reported to be an integral part of the defense against fungi. We have shown that the complement component ficolin-A significantly binds to Aspergillus conidia and hyphae in a concentration-dependent manner and was inhibited by N-acetylglucosamine and N-acetylgalactosamine. Calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 53 publications
4
43
0
Order By: Relevance
“…Specifically, it was shown that ficolin-2 stimulated murine macrophages to produce IFN-γ, IL-17A, TNF-α and IL-6 in vitro, and that ficolin-A KO mice exhibited decreased production of TNF-α and IL-17A in vivo upon stimulation with LPS [26]. Other investigators reported that ficolin-A increased the production of IL-8 from human lung epithelial cells following A. fumigatus challenge in vitro [29] . On the other hand, the same group showed that ficolin-A or ficolin-2 opsonization of A. fumigatus leads to decreased levels of IL-8, IL-1β, IL-6, and TNF-α from human monocyte-derived macrophages and neutrophils [30,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, it was shown that ficolin-2 stimulated murine macrophages to produce IFN-γ, IL-17A, TNF-α and IL-6 in vitro, and that ficolin-A KO mice exhibited decreased production of TNF-α and IL-17A in vivo upon stimulation with LPS [26]. Other investigators reported that ficolin-A increased the production of IL-8 from human lung epithelial cells following A. fumigatus challenge in vitro [29] . On the other hand, the same group showed that ficolin-A or ficolin-2 opsonization of A. fumigatus leads to decreased levels of IL-8, IL-1β, IL-6, and TNF-α from human monocyte-derived macrophages and neutrophils [30,34].…”
Section: Discussionmentioning
confidence: 99%
“…1a). Recent studies showed that ficolin-A opsonization of A. fumigatus conidia enhanced the binding of conidia to A549 airway epithelial cells [29], human monocyte-derived macrophages and neutrophils [30]. Consequently, hyphal growth was inhibited and fungal killing was increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three different ficolins exist in humans, ficolin-1 (FCN-1/M-ficolin), ficolin-2 (FCN-2/L-ficolin), and ficolin-3 (FCN-3/H-ficolin), while mice only possess an ortholog of human FCN-2, termed ficolin-A. Initial studies demonstrated that although ficolin-A opsonized A. fumigatus and had enhanced binding to human lung epithelial cells, ficolin-Aopsonized conidia did not lead to lectin pathway-specific C4 deposition [41] . Ficolin-A opsonized A. fumigatus did, however, augment human lung epithelial cell IL-8 production.…”
Section: Ficolinsmentioning
confidence: 99%